Road towards the construction of ontology of ontology of collective sports games - Pavicic, L.; Lozovina, M.; Lozovina, V.; Bonacic, Do. (Acta Kinesiologica, 2014)
A comparative analysis based on the analysis of the rules and practice games in four collective sports games (football, handball, basketball and water polo) generated the key terms exhaust all the aspects of games. Based on the comparative analysis of the rules we made the unification of four games through basic categories: space game, substrate, and the course of the game players. From the practice of playing unification was made for basic categories-terms arising from the flow of the game: Local / group skill (play the game), Tactics, Collectivistic, Match - Strategy and the game itself. These procedures were necessary to create a foundation on which to build ontology with the introduction of further hierarchical relationship all the possible connection between these concepts given as a prerequisite for the development of ontology`s on the computer.